Comparative Analysis of Swear Words in Uncut Gems Movie - Rail Mifta Zelira; Fitrawati Fitrawati (Universitas Negeri Padang, 2022)
This research aims to examine the functions, types, and differences in swear words between male and female in the Uncut Gems movie. The purpose of this research is to find out the types of swear words, the purposes, and the differences of swear words uttered by male and female characters in Uncut Gems movie. This research employed the descriptive-qualitative method. The data of this research were words, phrases, clauses, and sentences consisting of swear words which were selected from the dialogues of male and female characters in the Uncut Gems movie. While the source of data was the script of the Uncut Gems movie. This study showed that the use of swear words is dominated by the male characters compared to the female. The most dominant type of swear word used by both genders is emphasis. Male characters use swear words mostly to create attention while the female is to provide catharsis. Both male and female characters tend to be more aggressive when uttering swear words. However, when it comes to the variety and range of swear words themselves, it appears that male characters do use more than female characters. This research found that there are two types of swear words, stand-alone and slot-filler. Stand-alone has four functions expletive interjection, curses, unfriendly suggestion, and name-calling. The slot-filler also has four functions adjective/adverbial intensifier, the adjective of dislike, emphasis, and anaphoric use of epithet. At least five purposes of swear words were found to create attention, discredit, provoke, create interpersonal identification, and provide catharsis.